2023
DOI: 10.1038/s41598-023-49701-1
|View full text |Cite
|
Sign up to set email alerts
|

Soil bacterial community composition in rice-turtle coculture systems with different planting years

Ren Wang,
Weiwei Ma,
Dan Wu
et al.

Abstract: The rice-turtle coculture system is the most special rice-fish integrated farming system. In this study, we selected four paddy fields, including a rice monoculture paddy and three rice-turtle paddies with different planting years, to investigate the soil bacterial community composition with Illumina MiSeq sequencing technology. The results indicated that the contents of soil available nitrogen (AN), soil available phosphorus (AP) and soil organic matter (OM) in 9th year of rice-turtle paddy (RT9) were increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 21 publications
3
1
2
Order By: Relevance
“…Additionally, the feed for the frogs is also rich in nutrients, and this uneaten feed could also permeate the soil and increase its content of N. However, there was no significant difference in the content of AN among the three groups at the stage of rice maturity. This result is inconsistent with the results of some other studies, which indicated that rice–aquatic animal co-culture could increase the content of AN in this soil [ 31 , 34 , 37 ]. This could be due to frogs excreting nitrogen as urea or ammonia depending on their environment.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Additionally, the feed for the frogs is also rich in nutrients, and this uneaten feed could also permeate the soil and increase its content of N. However, there was no significant difference in the content of AN among the three groups at the stage of rice maturity. This result is inconsistent with the results of some other studies, which indicated that rice–aquatic animal co-culture could increase the content of AN in this soil [ 31 , 34 , 37 ]. This could be due to frogs excreting nitrogen as urea or ammonia depending on their environment.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, except for the high-density rice–frog co-cropping group (SG), the soil AP did not significantly increase in the rice maturity period compared with that before reclamation of the field. This is inconsistent with some previous studies in which the rice–aquatic animal co-culture mode significantly increased the content of AP in the soil [ 36 , 37 , 47 ]. This could be owing to the poor soil fertility and weak biological conditions of the reclaimed fields in this study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations